Navigating the Nexus: Exploring the Interplay of Populism, Trump’s Electoral Base, Climate Change Pessimism, and Immigration Skepticism - Awais, Muhammad (Annals of Human and Social Sciences, 2024)
This research investigates how Donald Trump leveraged pessimistic views on climate change and immigration to garner widespread support, and how his backing intensified these perceptions among his supporters. Various social and economic factors are attributed to the rise of populism while pessimistic views on climate change and immigration are often linked to ideological and structural reasons. A closer examination reveals that these pessimistic views align closely with support for Trump. Employing qualitative methods, the study delves into how Trump adeptly harnessed these views to build a strong support base. The findings indicate that Trump supporters typically hold pessimistic views on these key issues, and he effectively capitalized on sentiments to secure electoral victories. The study suggests that understanding the correlation between populist support and pessimistic views on climate change and immigration can provide valuable insights for political leaders to address these sentiments and foster a more positive public discourse.